Letter to the Editorial Board: Development Or Destruction of the World’s Society? - Bojarski, Włodzimierz W. (Problemy Ekorozwoju, 2011)
Despite numerous clear declarations of development and positive commitments, the rulers of this world: globalist structures, large capital, the US authorities and transnational corporations, continue without any significant changes to the current selfish, neo-colonial and robbery activities economy in the world. Thus, they have already made the choice indicated above and decided to follow the current disastrous path (crossing various threatening limitations), towards some catastrophe. To avoid it, it is necessary to change the system. It depends on all of us whether we will fight for the development of life and the common good, or whether we will be marginalized.